PENGARUH SYARIAH COMPLIANCE, TRANSPARANSI dan AKUNTABILITAS TERHADAP MINAT MUZAKKI MEMBAYAR ZAKAT DI DT PEDULI CABANG BOGOR: THE EFFECT OF SHARIAH COMPLIANCE, TRANSPARENCY AND ACCOUNTABILITY ON MUZAKKI'S INTEREST IN PAYING ZAKAT AT DT PEDULI BRANCH, BOGOR - Bukhori Hanief Al Fajry; Abrista Devi; Reni Sinta Dewi (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study aims to determine the influence of Sharia Compliance, Transparency, and Accountability on the interest of muzakki to pay zakat at DT PEDULI Bogor Branch. The problems experienced at DT PEDULI Bogor are the low collection of zakat funds and the number of those who have not reached their intended potential. This is influenced by the inequality between the potential of zakat funds and their realization, resulting in many muzakki who pay their zakat directly to mustahik and not through zakat institutions. The research approach used by the researcher is a quantitative approach. The population carried out in this study is the muzakki who give zakat at DT PEDULI Bogor branch with a total of 426 people. The sample collection method used is the purposive sampling method with a sample size of 100 respondents. The data analysis technique uses the Structural Equation Modelling-Partial Least Square (SEM-PLS) method through smartPLS 4.0 software. The results of this study show that Sharia compliance, and transparency have a significant and positive effect on the interest of muzakki in paying zakat. Meanwhile, accountability does not have a significant and positive effect on the interest of muzakki in paying zakat.